The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10228032
|View full text |Cite
|
Sign up to set email alerts
|

Droop Control Strategy of Utility-Scale Photovoltaic Systems Using Adaptive Dead Band

Abstract: This paper proposes a novel droop control strategy for addressing the voltage problem against disturbance in a transmission system connected with a utility-scale photovoltaic. Typically, a voltage control at the renewable energy sources (RESs) connected to the transmission grid uses a reactive power–voltage control scheme with a fixed dead band. However, this may cause some problems; thus, this paper proposes a method for setting a dead band value that varies with time. Here, a method for calculating an approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…There are various approaches for controlling the reactive power in the scientific literature (Ku et al, 2015;Ghosh et al, 2016;Mahmud and Zahedi, 2016;Molina-García et al, 2016;Zhang et al, 2017;Kim et al, 2020;Li et al, 2020;Ceylan et al, 2021;Wagle et al, 2021). In most studies, reactive power control is achieved in centralised, distributed, and decentralised forms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are various approaches for controlling the reactive power in the scientific literature (Ku et al, 2015;Ghosh et al, 2016;Mahmud and Zahedi, 2016;Molina-García et al, 2016;Zhang et al, 2017;Kim et al, 2020;Li et al, 2020;Ceylan et al, 2021;Wagle et al, 2021). In most studies, reactive power control is achieved in centralised, distributed, and decentralised forms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Metode kontrol primer yang saat ini diimplementasikan pada inverter baterai komersial adalah metode kontrol droop [14]- [17]. Untuk mengoptimalkan pengontrol dengan metode droop perlu ditentukan nilai koefisien droop yang sesuai.…”
Section: Pendahuluanunclassified
“…Untuk mengoptimalkan pengontrol dengan metode droop perlu ditentukan nilai koefisien droop yang sesuai. Pada penelitian ini nilai koefisien tersebut ditentukan dengan menambahkan dead band pada tegangan nominal [15], [17], [18]. Keterkaitan penelitian ini dengan beberapa penelitian tentang kontrol primer menggunakan metode kontrol droop dapat dilihat pada Tabel 1.…”
Section: Pendahuluanunclassified
“…The obtained results confirm the current highlights of other similar studies, i.e., that the storages for self-consumption only are not profitable until the average price of energy storage devices becomes lower than 256 €/kWh (including the inverter price). Kim et al [7] propose a novel droop control strategy for setting a dead band value that varies with time in order to address the voltage problem against disturbance in a transmission system connected with a utility-scale PV system. Simulation results showed that an adaptative dead band, rather than a fixed one, is able to perform a flexible system operation against disturbance.…”
Section: Plants Based On Photovoltaic (Pv) Panels and Battery Energy ...mentioning
confidence: 99%
“…Considering this background, the studies collected in this Special Issue cover the following topics: (i) the analysis of plants based on photovoltaic (PV) panels and battery energy storages, investigating the use of electric vehicles [3], the coupling of these systems with a single hydropower plant for renewable energy communities [4], the assessment of the impacts of these plants on the effectiveness of electric distribution grids [5], their economic evaluation in residential applications for islands not electrically connected to the mainland [6], and the development of novel control strategies to address voltage disturbance in transmission systems connected with PV systems [7]; (ii) the economic analysis of a novel floating offshore wind structure, built with concrete [8]; (iii) the power to synthetic natural gas (PtSNG) plants to store intermittent renewable sources [9]; (iv) a low-cost secured distributed Internet of Things (IoT) system for monitoring and controlling appliances/devices connected in a polygeneration microgrid supplied by renewable technologies [10] as well as the optimization of both independent energy systems, ensured by the integration of the thermal/electric energy systems and renewable energy systems [11], and of building energy consumption by means load forecasting methodologies [12].…”
Section: Introductionmentioning
confidence: 99%